Optimum spatial variable blank holder forces determined by the sequential response surface method (SRSM) and a hybrid algorithm - Sener, Bora; Yurci, Mehmet Emin; Bogoclu, Muharrem (CARL HANSER VERLAG, 2019)
The blank holder force (BHF) plays an important role in the control of material flow. Low BHF leads to wrinkling, while high BHF leads to tearing at the part in the deep drawing process. Therefore, BHF control along the blank periphery is very crucial for the success of the deep drawing process. In this paper, spatial variable blank holder forces in the deep drawing of a double bowl sink were predicted by using a method based on a sequential response surface and hybrid algorithm. Predicted blank holder forces from the method were verified on a multipoint control hydraulic press and a 26 % improvement in the minimum thickness of the part formed as compared to the BHF constant was obtained.
Keywords: Blank holder force; response surface method; hybrid algorithm; thinning; DEEP-DRAWABILITY; OPTIMIZATION; Materials Science